O papel do gestor da Educação Infantil na formação docente centrada na escola - Pomilho, Sheila de Souza (2022)
The qualitative approach research has analyzed, as a general target, the role of management in school-centered teacher training in the context of Early Childhood Education. It has also developed the following specific objectives: set the public policy in early childhood education for school management historically; describe the specificity of a manager's role in early childhood education and its relationship with a team formation and identify how school management can contribute to the development of training processes school-centered. The specific objectives of the research gave conditions to characterize the group of participating managers. Therefore, we analyzed their conceptions and legislation on school administration in early childhood education, as well as the specificities of the position in teacher training. The data collection instrument was established according to autobiographical research, using the narrative interview, having interviewed two public and private kindergarten school managers. The results showed that the work of the school management for school-centered teacher training is a promising path for democratic and collaborative administration. Transforming the school into an environment that values teacher training requires understanding childhood and the aspects that involve teacher professionalization. In this way, for the principles of coaching in context to be a daily practice in schools, it is necessary to develop management tools and systematize training plans as part of the curricular proposal